PENGARUH PEMBERIAN TEPUNG CACING TANAH (Lumbricus sp.) SEBAGAI ATRAKTAN DALAM PAKAN TERHADAP TINGKAT KONSUMSI PAKAN, EFISIENSI PAKAN DAN PERTUMBUHAN IKAN PATIN (Pangasius sp.) - Rizkiana Amalia; Sri Hastuti; Agung Sudaryono (Departemen Akuakultur FPIK UNDIP, 2019)
Catfish (Pangasius sp.) is a dominant consumption fish and it is targeted that production will be increase every year. Catfish have a low feed efficiency value which is causes the growth of catfish to be less optimal, so it is necessary to add ingredient into the diets so that the fish are interested in eating the diets given. The use of earthworm meal as an attractant was expected to increase of feed consumption, feed efficiency and growth of catfish. This experiment aimed to study the effect of dietary earthworm meal as an attractant on feed consumption level, feed efficiency and growth of catfish (Pangasius sp.). The catfish used with an initial average body weight of 6,78±0,68 g/fish. The fishes were cultured in the aquarium for 42 days with the stocking dencity of 1 fish/2L. The experimental method used was completely randomize design (RCD) with 4 treatments and 3 replicates. The treatments were addition of earthworm meal (Lumbricus sp.) as an attractant with a dose of 0%, 5%, 10% and 15% in the diets. The data showed that the use of earthworm meal (Lumbricus sp.) inclusion in the diets resulted in significant effects (P <0,05) on feed consumption (159,73 g), FE (81.06%), PER (2,31%), G (9,76 g) and SGR (1,97%/day) but not significant effect (P>0,05) on survival rate (84.44-93,33%). The best food preference test in treatment C dose 10% of earthworm meal with percentage 44% fish approaching diets. The water quality parameters during this study varied between suitable range for the catfish (Pangasius sp.) life, i.e temperatures 27,70-30,900C; pH 7,00; DO 5,37-5,52 mg/L and NH3 0,0036-0,0095 mg/L. It was concluded that catfish (Pangasius sp.) fed with the diet containing 10% attractants of earthworm meal resulted in better feed consumption, feed efficiency and growth.